Musical discourse in the theory of musical semiotics - Mitić, Marjan D. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2021)
Music is an abstract language that is constantly evolving, and in this connection, one of the possible approaches to the interpretation of music as a discourse concerns the issues of the relatedness of music and speech, that is, the language of music and language of speech. In this way, the relationship between musical discourse and the musical thought of the composer and speech as a product arising from the opinions of the speaker is established. In this paper, through the examination of discourses on music as a product of human activity, which are recognized in different cultures in different ways, one considers the way in which individual works, the phenomenon of music and the forms of human behavior caused by music can be interpreted. The aim of the paper is to emphasize the importance of a generative approach to the understanding of tonality through a critical consideration of the semiological approach for understanding the language of music, and to provide an insight into the similarities between music and language.Key words: discourse, music as a discourse, theory of musical semiotics, musical discourse in semiotics theory
Keywords: discourse; music as a discourse; theory of musical semiotics; musical discourse in semiotics theory